Review of Moroccan Cannabis sativa L.: Cultivation, phytochemistry, therapeutic uses, and biological activities in in-vitro, in-vivo and in-silico assays - El Oihabi, Maryem; Mehdi, Imane; Mbarek, Ouabou; Mdarhri, Yousra; Ghanimi , Soufiane; Ben Allal , Laïla; Fakih Lanjri , Asmaa; Ammari , Mohammed (Ethnobotany Research and Applications, 2025)
Background: Cannabis sativa’s medicinal properties have been known for many cultures. Numerous plant parts have long been utilized in ethnomedicine due to their complexity. This study aimed to compile existing documents on Cannabis sativa in Morocco. We reviewed the history, scientific research, extraction procedures, diversity of phytochemicals, traditional uses, and experimental assays. Methods: To achieve our goal, we utilized proper keywords related to the topics and compiled the bibliography using electronic survey databases and engines, including Scopus, ScienceDirect, PubMed, Public Library of Science, JSTOR, Google Scholar, Web of Science, and the WSU online database (PubChem). The papers were searched for a period from 1912 to 2024 using French, English, and Spanish. Results: Results showed that 2017 documents have addressed Cannabis sativa in Morocco, including scientific articles, theses, conference papers, books, and reports. These documents demonstrated that six varieties, including ‘Khardala’, ‘Critical’, ‘Amnésia’, ‘Beldia’, ‘Gorilla’, and ‘Pakistana’, are cultivated in Morocco, mainly in Northern provinces such as Chefchaouen, Taounate, Larache, Al Hoceima, and Tetouan. Essential oils and extracts of Cannabis sativa are rich in chemical compounds; 32 and 24 molecules, respectively. Bioactive molecules, which include polyphenols, flavonoids, terpenes, and cannabinoids, vary depending on the variety, the organs used, the extraction approaches, and the growing areas. They are mainly extracted by hydrodistillation from aerial parts, while extracts are isolated by maceration, sonification, and decoction from seeds and aerial parts. Further, in-vivo, in-vitro, and in-silico assays confirmed the biological activities of Cannabis sativa L., mainly anti-microbial, anti-parasitic, anti-inflammatory, and anti-cancer effects. Conclusions: This study is the first to review the topics related to Cannabis sativa L. in Morocco and offer new and compiled data in North Africa and the Mediterranean basin. Keywords: Cannabis sativa L., Moroccan varieties, scientific research, extraction of biomolecules, medicinal uses, biological activities.